PENGGUNAAN MODEL HIDROLOGI DI SUB DAS CILIWUNG HULU - Yustika, Rahmah Dewi (Informatika Pertanian, 2014)
A watershed has complex hydrological components and may be difficult to understand comprehensively. Modelling can be used to simplify and predict the processes which will happen. SWAT (Soil and Water Assessment Tool) is a model which can predict hydrology and simulate various processes in watershed.The objective of this research was: to analyse performance of SWAT model which predict discharge flow in upper Ciliwung watershed through calibration. Methods applied included analysis of the input data and calibration. The research was conducted in the period of June 2011 until June 2012. Based on the data of daily discharge flow in February and March 2008 and 2009, the calibration results showed values of R 0,80 and NSE 0,55. These results described that SWAT model can be used to predict hydrological processes in upper Ciliwung watershed.Prediction of hydrology could be used as the base to manage land agriculture towards sustainable agriculture.